Problems Of Implementing Assessment Of Students With Special Needs In Elementary Schools Providing Inclusive Education - Mirnawati; Jaleha, Siti (Journal of Education for Sustainability and Diversity, 2024)
The purpose of this study was to obtain an overview of the problems faced or felt by teachers in the implementation of the assessment of students with special needs in primary schools providing inclusive education. This study uses a qualitative approach with a descriptive type of research. Sources of data in this study were teachers at SDN Semangat Dalam 1 Batola. Data collection techniques used interviews, questionnaires, and documentation. Data analysis used the Miles and Huberman model which consisted of data reduction, data presentation and conclusion drawing. The data validity technique uses member checks and triangulates data sources. The results of the study indicate that there are several problems or problems faced and felt by teachers in the implementation of the assessment of students with needs at SDN Semangat Dalam 1 Batola at this time, namely 1) the teacher's low understanding of the concepts and procedures for compiling comprehensive assessment instruments for children with special needs; 2) low participation of parents/families of students with special needs in providing information when collecting information on assessment implementation; 3) the teacher's low understanding in carrying out the analysis of the assessment data.